Heads in the clouds: On the carbon footprint of conference‐seeded publications in the advancement of knowledge - Laurent Seuront (Wiley, 2021)
Abstract The carbon footprint of flying overseas to conferences, meetings, and workshops to share and build knowledge has been increasingly questioned over the last two decades, especially in environmental and climate sciences, due to the related colossal carbon emissions. Here, we infer the value of scientific meetings through the number of publications produced either directly or indirectly after attending a scientific conference, symposium, or workshop (i.e., the conference‐related production) and the number of publications produced per meeting (i.e., the conference‐related productivity) as proxies for the academic value of these meetings, and relate them to both the number of meetings attended and the related carbon emissions. We show that conference‐related production and productivity, respectively, increase and decay with the number of meetings attended, and noticeably that the less productive people exhibit the largest carbon footprint. Taken together, our results imply that a twofold decrease in the carbon footprint FCO2 of a given scientist would result in a twofold increase in productivity through a fivefold decrease in the number of meeting attended. In light of these figures, we call for both the implementation of objective and quantitative criteria related to the optimum number of conferences to attend in an effort to maximize scientific productivity while minimizing the related carbon footprint, and the development of a rationale to minimize the carbon emission related to scientific activities.